Economic Scheduling Problem of Nanomaterial Import and Export Trade Based on Redundant Data Compression Algorithm and Its Parameter Adjustment Method - Lihong Lu; Daixin Wang (Advances in Materials Science and Engineering)
In the context of today’s supply-side structural reform, the research on the relationship between foreign trade and economic growth has received extensive attention from researchers. Since China’s economic reform and opening up in the late 1970s, China’s economy has experienced a relatively long period of rapid growth. From 1978 to the end of 2008, China’s economy grew at an average annual rate of about 10%, and its GDP grew from US$9.75 billion in 1978 to US$1,430.69 billion in 2008. The progress is amazing, the total import and export of goods increased from 20.64 billion US dollars in 1978 to 25.6326 billion US dollars in 2008, and the world ranking rose from 32nd in 1978 to 3rd in 2008, second only to the United States and Germany. The analysis of the test results presented in this paper shows that, from 1995 to 2014, China’s average annual exports accounted for 23.72% of GDP. Since China joined the World Trade Organization in 2001, China’s share of export trade has increased significantly. In 2004, the total value of exports reached 4910.33 billion yuan, equivalent to more than 29% of China’s GDP, and continued to rise in the following years. China’s total exports as a share of GDP declined between 2009 and 2014 but remained above 20% in both cases.